Research on Chinese Intelligent Guanglianda in High-rise Construction - Romanovich Marina; Shi Peiyu; Wang Ziyue; Zhao Liang; Gerasimova Vera (E3S Web of Conferences, 2018)
Since the reform and opening up in China, the rapid development of China's construction industry, especially after 2011, BIM technology in China has a rapid development and depth of application. This article mainly discusses the process of development of China's construction industry management and the process of development of BIM technology in China and, the use of software in China, the main use of revit in 3D modeling (design stage), the use of Guanglianda in the whole process of construction management. This article researches on Guanglianda and the applications were described, for example, in the integrated project of management information, labor management information, construction video surveillance, material management, material site acceptance. This paper also elaborates on the cooperation of Revit and Guanglianda in different stages. This paper also elaborates on a construction case in China, and makes a description of the problems of crane, facts and time, and then explores the reasons behind the rapid construction of China. And the feasibility of China's construction management approach to the introduction of Russia.